Exploring The Impact of Corporate Social Responsibility on Financial Performance with Green Innovation as a Mediator - Prameswari, Aprilia; Kusumaningtias, Rohmawati (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Corporate Social Responsibility and green innovation are key resources and strategies for improving corporate financial performance and sustainability. This study aims to examine the relationship between CSR, green innovation, and financial performance through a literature review. This study reviews various previous studies that explain how CSR practices encourage companies to develop environmentally friendly innovations that can influence financial performance. The results of the analysis show that CSR has a positive impact on financial performance either directly or through green innovation. However, the effect of green innovation on financial performance varies depending on the business sector and the level of effectiveness of its implementation. Overall, CSR and green innovation not only improve financial performance but also strengthen long-term sustainability in business practices